Continuous Ambulatory Peritoneal Dialysis-Related Peritonitis: Clinical Characteristics, Etiological Agents and Their Antibiotic Susceptibilities - Sagmak-Tartar, Ayse; Ozden, Mehmet; Akbulut, Ayhan; Demirdag, Kudbettin; Ozer-Balin, Safak (Aves, 2016)
Objective: The objective of this study was to determine clinical characteristics, etiological agents, and their antibiotic susceptibilities in continuous ambulatory peritoneal dialysis (CAPD)-related peritonitis encountered in our hospital. Methods: Thirty patients with peritonitis attack among 55 adult patients aged >= 18 years, who applied to Nephrology Clinic of Firat University Hospital between January 2012 and February 2013 and who were monitored in the CAPD unit were included in this prospective study. Cultures were performed on both solid media and blood culture bottles according to the recommendations of International Society for Peritoneal Dialysis. Antibiotic susceptibilities were investigated by disk diffusion method. Results: During clinical evaluation, abdominal guarding (n=28, 93.3%), rebound tenderness (n=4, 13.3%), fever (n=9, 30%), nausea and vomiting (n=13, 43.3%), and diarrhea (n=5, 16.7%) were detected. Turbid dialysis fluid and abdominal pain were noted in all patients. Direct Gram staining yielded positive result in 1 (3.3%) patient. In 28 (93.3%) patients bacterial growth was detected in the cultures. Bacterial growth was detected on solid culture media in 14 (46.7%), and blood culture bottles in 28 (93.3%) patients. In 2 (6.7%) patients, bacterial growth was not detected in both media. The same microorganisms were identified in both methods, and their antibiograms yielded similar results. Gram-positives included coagulase-negative staphylococci (n=16, 57.1%), Staphylococcus aureus (n=4, 14.3%), streptococci (n=4, 14.3%), and enterococci (n=1, 3.6%). Gram-negatives consisted of Escherichia coli (n=2), and Yersinia enterocolitica (n=1). In 46.2% of Gram-positive microorganisms penicillin resistance was detected, while 9.5% of staphylococci were methicillin-resistant. Conclusions: Each health center should have knowledge of its prevalent microbial agents, and their susceptibility profile, which is essential for the determination of suitable alternative empirical treatment. This strategy will obviate unnecessary use of antibiotics, and contribute to the decrease in the potential development of antibiotic resistance.
Sürekli ayaktan periton diyaliziyle ilişkili peritonit: Klinik özellikler, etken mikroorganizmalar ve antibiyotik duyarliliklari
Keywords: Continuous ambulatory peritoneal dialysis; peritonitis; anti-bacterial agents